The Arctic Nearshore Turbidity Algorithm (ANTA) - A multi sensor turbidity algorithm for Arctic nearshore environments - Klein, Konstantin; Lantuit, Hugues; Heim, Birgit; Doxaran, David; Juhls, Bennet; Nitze, Ingmar; Walch, Daniela; Poste, Amanda; Søreide, Janne (Science of Remote Sensing, 2021)
International audience